Global Regulations for a Digital Economy: Between New and Old Challenges. Issue 4 (10th May 2020) - Beaumier, Guillaume; Kalomeni, Kevin; Campbell‐Verduyn, Malcolm; Lenglet, Marc; Natile, Serena; Papin, Marielle; Rodima‐Taylor, Daivi; Silve, Arthur; Zhang, Falin
Abstract: Digital technologies are often described as posing unique challenges for public regulators worldwide. Their fast‐pace and technical nature are viewed as being incompatible with the relatively slow and territorially bounded public regulatory processes. In this paper, we argue that not all digital technologies pose the same challenges for public regulators. We more precisely maintain that the digital technologies' label can be quite misleading as it actually represents a wide variety of technical artifacts. Based on two dimensions, the level of centralization and (im)material nature, we provide a typology of digital technologies that importantly highlights how different technical artifacts affect differently local, national, regional and global distributions of power. While some empower transnational businesses, others can notably reinforce states' power. By emphasizing this, our typology contributes to ongoing discussions about the global regulation of a digital economy and helps us identify the various challenges that it might present for public regulators globally. At the same time, it allows us to reinforce previous claims that these are importantly, not all new and that they often require us to solve traditional cooperation problems. Abstract : A good understanding of the different regulatory challenges posed by different digital technologies is necessary but on its own insufficient. Global cooperation is badly needed, and international organizations have a key role to play in promoting shared understandings. This is even more essential as no public regulators have the capacity to single‐handedly solve all regulatory challenges raised by digital technologies.